About the Efficacy of Virtual and Remote Laboratories in STEM Education in Secondary School: A Second-Order Systematic Review - Daniela Fadda; Carole Salis; Giuliano Vivanet (LED Edizioni Universitarie, 2022)
Online laboratories brought new opportunities for instruction. In this work, a secondorder systematic review about the efficacy of virtual and remote labs on learning in high school STEM education is presented. Nine systematic review and a meta-analysis were included. A descriptive summary (qualitative and quantitative) of their findings is provided. On average, online laboratories support learning to an extent comparable to that observed in real labs; their effect is even more positive when they are integrated into more traditional teaching practice (e.g., as pre-lab practice sessions before the hands-on experiments) and when they are supported by adequate teacher feedback. Content knowledge is the learning outcome most often assessed; while practical and inquiry skills related to scientific reasoning are investigated less frequently. The results are promising for instructional design and for the future research, despite the data variability and some methodological limitations of individual studies (lack of relevant quantitative data, such as effect sizes and moderator analysis). Further experimental research is required to estimate the effect of online labs on different learning outcomes and to better understand the moderating role of some variables related to interventions and students.